110k views
5 votes
Solve 6/×-3 =x/3

for x, and determine if the solution is extraneous or not.
x = -2. extraneous
x = -2, non-extraneous
X = -3. non-extraneous
x = -3. extraneous​

1 Answer

5 votes

Answer:

X = -3. non-extraneous

Explanation:

The given equation is
(6)/(x-3) =(x)/(3)

We cross multiply to get:


6*3=x(x-3)

Expand and multiply.


18=x^2-3x


x^2-3x-18=0

We factor to obtain:


(x-6)(x+3)=0


x=-3,x=6

Checking for extraneous solutions

Substitute x=-3
(6)/(-3-3) =(-3)/(3)


(6)/(-6) =(-3)/(3)


-1=-1


1=1.....Non-extraneous

Checking for x=6


(6)/(6-3) =(6)/(3)


(6)/(3) =(6)/(3)


2=2....Non-extraneous

User Manuel Schweigert
by
6.2k points